Participation in Academic Administration of Teachers in Schools under the Sai Mai District Office, Bangkok Metropolitan - อนันธรรมกุล, ธิติกร; รักษนคร, กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) study the participation in academic administration of teachers in educational institutions; 2) compare the participation in academic administration of teachers in educational institutions, classified by educational level, work experience, and size of the educational institution; and 3) study the guidelines for developing participation in academic administration of teachers in educational institutions under the Sai Mai District Office, Bangkok. The sample comprised 241 teachers. The sample size was determined using Taro Yamane’s table, and the participants were selected through stratified random sampling according to school size. The research instrument was a five-point Likert scale questionnaire, with the index of item-objective congruence (IOC) ranging from .80 to 1.00 The overall reliability of the questionnaire was 0.964. The statistics employed for data analysis included frequency, percentage, mean, standard deviation, t-test, one-way analysis of variance (ANOVA), and content analysis.            The results of the research found that 1. The overall level of teachers’ participation in academic administration in schools under the Sai Mai District Office, Bangkok, was found to be high. The aspect with the highest mean score was the development of internal quality assurance systems and educational standards, followed by instructional management within schools. In contrast, the aspect with the lowest mean score was measurement, evaluation, and credit transfer, respectively. 2. The results of the comparison of participation in academic administration of teachers in educational institutions, classified by educational level, work experience, and size of the educational institution, showed overall significant differences. 3. Guidelines for teachers’ participation in academic administration in educational institutions should be implemented as follows: In terms of measurement, evaluation, and credit transfer, schools should establish diverse, transparent, and fair assessment policies to ensure that assessment practices accurately align with the intended objectives. Furthermore, collaborative meetings between administrators and teachers should be organized to jointly determine appropriate assessment criteria.